Cytokines and Onchocerciasis-Associated Epilepsy, a Pilot Study and Review of the Literature - Carter, Jane (Pathogens, 2021)
Neuro-inflammation may be associated with onchocerciasis-associated epilepsy (OAE) but thus far very few immunological studies have been performed in children with this form of epilepsy. In a pilot study we measured the cytokine levels in cerebrospinal fluid (CSF) of persons with OAE from Maridi, South Sudan, and from Mosango, Democratic Republic of the Congo (DRC) and compared these results with cytokine levels in CSF of Africans with non-OAE neurological disorders, and Europeans with epilepsy or other neurological conditions. The following cytokines were studied: IL-6, TNF-α, IL1-β, IL-5, IL-4, IL-13, CCL3 (Mip-1α), VEGF-C, VCAM-1. No cytokine was significantly associated with OAE, although a lower IL-13 level was observed in CSF of persons with OAE compared to African controls. Observed cytokine profiles and neuro-inflammation may be the consequence of long-standing epilepsy, concomitant infections and malnutrition. Ideally cytokine levels should be determined in a prospective study in serum and CSF collected at the time of onset of the first seizures.
Keywords: cerebrospinal fluid; cytokines; onchocerciasis-associated epilepsy.